Pelaksanaan Bimbingan Kelompok Untuk Menumbuhkan Solidaritas di Kelas Viii-A SMP Guppi Palangka Raya: Implementation Of Group Guidance To Grow Solidarity In Class VIII-A Guppi Palangka Raya Middle School - Ocky Dewi Susanti; Andi Riswandi Buana Putra (Suluh: Jurnal Bimbingan dan Konseling, 2017)
The purpose of this study was to find out the form of solidarity of students in class VIII-A and Implementation of Group Guidance in Growing Solidarity in Class VIII-A GUPPI Middle School Palangka Raya. The approach used in this study was to use qualitative methods, while data instruments were used are observation, interviews, and documentation. The objects in this study are BK teachers, Principals, Deputy Principals for Student and Student Fields. Analysis of the data used by using case studies. The results showed that group guidance services had been carried out and carried out in the GUPPI Palangka Raya Middle School and group guidance services could be used as a forum for students to get closer and foster a sense of solidarity in class VIII-A, because through group guidance students could overcome the problem of solidarity and realize this solidarity by instilling a sense of empathy, a sense of togetherness, cooperation, mutual respect and tolerance for students. So that students can apply the values ​​of solidarity in their daily lives both in socializing in the school environment or socializing in their daily living environment.